Pre and Present COVID-19 Situation: A Framework of Educational Transformation in South Asia Region - Sunjida Khan; Nurul Mohammad Zayed; Saad Darwish; Vitalii Nitsenko; K. M. Anwarul Islam; Md. Arif Hassan; Oksana Dubrova (Emerging Science Journal, 2023)
This study is designed to support the development of strategies to recover from the disrupted impact of COVID-19 on HE institutes of the South Asian Region (SAR), as the nations in this region are severely cursed by poverty and unemployment. During the unusual phase of the COVID-19 pandemic, the face-to-face learning method is no longer appropriate, and the crisis leads to force on distance learning instead of physical learning. Like all other educational institutions, HE institutions are also in big trouble. Changes in educational structure change the pattern of academic work, which may have an inverse impact on acquiring knowledge and improving skills. Not only students but also a greater number of teachers at the HE institutions required to continue their service through online during this closure period. However, well digital infrastructure and digital contents appear to be the prime requirements for this educational transmission, which are extensively accessible in SAR countries. By following a mixed-methods strategy, the study specifically examines the impact of the pandemic on higher education in the South Asian Region, with an emphasis on the impact on learners, educators, and institutions, and to identify the measures that have been taken by these countries to survive and continue the education system with all the obstacles of the crisis. It concludes with some vital suggestions that may be applied to mitigate the crisis moment and assist in moving forward with more technological advancements for a new future. Doi: 10.28991/ESJ-2023-SPER-06 Full Text: PDF